Bimbel Privat Rumahan: Investasi Cerdas untuk Masa Depan Anak - Nadia Hidayahtul Jannah; Zuana, Megantara; Syifa Amalia Putri; Veronica Intan Susanti; Heryanto Susilo; Desika Putri Mardiani (JPUS: Jurnal Pendidikan Untuk Semua, 2024)
This article discusses the role of private tutoring at home as a solution to overcome student learning difficulties. This research uses a descriptive qualitative approach with a focus on Mrs. Cicik's tutoring in Simokerto Village, Surabaya. This research aims to describe the learning process, learning methods, obstacles, solutions, and evaluation of learning methods applied in the tutoring. The results showed that Bu Cicik's tutoring serves students from kindergarten to elementary school with learning methods tailored to the needs and characteristics of each student. The methods used include writing, parable, and spelling methods for kindergarten students, as well as special tricks to solve math problems for elementary school students. However, this tutoring also faces some obstacles, such as the different ways of understanding students and students' difficulties in understanding the material taught at school. Ms. Cicik overcomes these obstacles by understanding how each student learns, simplifying complex concepts, and applying diverse evaluation methods to monitor student progress. This study concludes that private home tutoring like Mrs. Cicik's can be an effective alternative to overcome students' learning difficulties. Flexible, individualized learning methods that focus on students' personal needs are proven to help improve understanding and motivation